0442 Occupational exposures and parkinsonism among women textile workers in shanghai, china. (21st August 2017) - Ilango, Sindana; Li, Wenjin; Tanner, Caroline; Hu, Shu-Ching; Ray, Roberta; Nielsen, Susan Searles; Gao, Dao Li; Wang, Xin; Costello, Sadie; Thomas, David B; Checkoway, Harvey
Abstract : Objective: To examine the association of endotoxin and other occupational exposures with parkinsonism (PS) severity and progression of PS signs. Methods: Movement disorder specialists examined 823 retired female textile workers ages 51–86 in Shanghai, China for PS prevalence and assessment of Unified Parkinson Disease Rating Scale motor subsection part 3 (UPDRS3). Most (n=669) were re-evaluated two years later. Occupational exposures to endotoxin, metals, solvents, magnetic fields, and shiftwork during a mean of 24 years working in the textile industry were assessed from detailed work histories and a job exposure matrix. We examined the association between each exposure and PS, severity (UPDRS3 score), and progression (annual change in UPDRS3) with multivariable regression models adjusting for age, smoking, and examiner. Results: We observed 39 prevalent PS cases and 784 non-cases. No association was observed between endotoxin and PS prevalence, disease severity, or disease progression. The other chemical occupational exposures and magnetic fields also had had no associations with PS prevalence or disease severity. Shiftwork was marginally positively associated with disease progression. For each year of shiftwork as of the baseline exam, UPDRS3 score increased annually by an additional 0.047 (95% CI: −0.003, 0.097). Conclusions: We observed little evidence for an association between endotoxin and other occupational exposures with PS in this cohort of textile industry workers, although we are unable to rule out the possibility of clinically modest increases in progression among workers who had experienced several years of shiftwork.